Yoga To Improve Women’s Sexual Function - Winda Nurmayani; Syamdarniati Syamdarniati; Ilham Ilham (Poltekkes Kemenkes Surakarta, 2022)
Background: Sexual function in women is closely related to women's reproductive health, if an individual experiences a disturbance in his sexual function, his reproductive function must also have problems. This sexual problem can be overcome by exercising, one of the recommended sports is yoga, Yoga is a sport that can improve sexual function and treat sexual disorders so that it can overcome sexual function problems. Aim of study is to analyze effect yoga to improving women's sexual function. Methods: A Descriptive cross-sectional, wiyh population were women who have been married, aged 20-45 years, yoga regularly. Amount of sample is 60 respondent, choosen using total sampling technique. The instrument used is the FSFI (Famale Sexuale Function Index) questionnaire, which is a questionnaire to measure sexual desire, sexual arousal, vaginal lubrication, orgasm, sexual satisfaction and pain. Data were analize using Chi-Square Test. Results: Analysis Chi Square test with p-value 0.000, its mean p value <0.05. Yoga 25 times can improve the women’s sexual function. Conclusion: Yoga is associated with women’s sexual function. Women whoare married or have a partner can do yoga regularly because yoga has benefits for health and improves the sexual qualityof women.